Industrially produced trans fat and saturated fat content of food products in Jamaica - Rasheed Perry; Fitzroy J. Henry; Dwyte Bremmer (Pan American Health Organization, 2023)
Objective. To estimate industrially produced trans and saturated fatty acid levels in foods within the Jamaican food system. Methods. A total of 308 commonly consumed foods were selected for analysis based on their potential to contain trans fatty acids. Samples were collected from supermarkets, convenience stores, and fast-food restaurants. Official methods of gas chromatography for the analysis of fats were used. The results were expressed as grams of fatty acid per 100 g of food sample and percentage of total fatty acids. Results. Total fat was found to exceed United Kingdom National Health Service (NHS) limits in 27.3% (n = 84/308) of food samples. About one-third (33.8%; n = 104/308) of commonly consumed foods in Jamaica contained varying levels of industrially produced trans fatty acids, while 7.8% exceeded the Pan American Health Organization limit of 2% of total fat. Industrially produced trans fatty acids were found in food categories such as canned meats, baked goods, cooking oils, condiments, breakfast cereals, desserts, dairy, spreads, snacks, and confectionery. The subcategories coconut oils and burgers had the highest mean content. Canned food, infant food, and pasta categories had no trans fat present. Saturated fats were found in almost all foods. Importantly, 32.5% (n = 100/308) of the foods had saturated fat concentrations higher than the NHS limit of 5 g per 100 g of food. Most of the food items with high levels of industrially produced trans fatty acids also contained high levels of saturated fats. Conclusions. Food products in Jamaica contain varying levels of fats that exceeded recommendations which support healthy consumption. Further exploration and reformulation efforts are needed to ensure that nutritional qualities are improved.